2021
DOI: 10.6007/ijarbss/v11-i5/9856
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Technostress on Emotional Exhaustion and Coping Strategies

Abstract: Technostress at a workplace is a negative consequence of not being able to adapt adequately to technology rapid advancement. It may cause psychological disturbance to the employees and lead to many disturbing effects such as job dissatisfaction, job isolation and emotional exhaustion. While past studies have examined the causal direction of technostress to employees' behavior, this study explores the relationship between technostress and emotional exhaustion and coping strategy, measured as proactive and react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Moreover, the current study has provided evidence that teachers are experiencing technostress. According to Kassim et al [17], individuals experiencing technostress also experience emotional exhaustion. This warrants interventions that will help teachers manage these emotions and psychological challenges to function and perform their tasks to their fullest potential [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the current study has provided evidence that teachers are experiencing technostress. According to Kassim et al [17], individuals experiencing technostress also experience emotional exhaustion. This warrants interventions that will help teachers manage these emotions and psychological challenges to function and perform their tasks to their fullest potential [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, job satisfaction and loneliness are caused by technostress which has a domino effect on proactive and reactive coping. The study of Kassim et al [17] suggested a significant relationship between technostress and emotional exhaustion, leading to poor work performance. However, the study's coping methods were not evident, and researchers recommended further investigation of what form of intervention was most suitable.…”
Section: Literature Reviewmentioning
confidence: 99%